PENGARUH MODAL USAHA, LOKASI USAHA, TEKNOLOGI INFORMASI, DAN LAMA USAHA TERHADAP PENDAPATAN USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) DI KABUPATEN BOYOLALI - Wulan Widia Astutik; Suhesti Ningsih; Sri Laksmi Pardanawati (CV. Denasya Smart Publisher, 2024)
This study aims to determine the effect of business capital, business location, information technology, and length of business on the income of micro, small and medium enterprises (MSMEs) in Boyolali Regency. This study used a quantitative type of research. The data in this study is primary data. Data collection was carried out by distributing questionnaires to MSME actors in Boyolali Regency. The population in this study is MSME actors in 22 sub-districts in Boyolali Regency. The number of samples was calculated using the slovin formula with the results of 100 respondents. The data obtained is then processed using SPSS with data analysis methods, descriptive statistical tests, data quality tests consisting of validity tests and reliability tests, classical assumption tests used are normality tests, multicollinearity tests and auto correlation tests. The feasibility test of the model used is the F test. While the hypothesis test used is a multiple linear regression test, t test, and determination coefficient test. The results showed that the independent variables of business capital, business location, information technology and length of business each partially had a positive and significant influence on the income of MSMEs in Boyolali Regency.